Applying Evolutionary Economic Geography beyond case studies in the Global North: Regional diversification in Vietnam. Issue 1 (23rd December 2021) - Breul, Moritz; Pruß, Fabio
Abstract : Hitherto, the path‐dependent understanding of regional diversification in Evolutionary Economic Geography (EEG) has drawn largely on insights into industrialized countries. However, in the past few decades several regions in the Global South have undergone rapid structural transformations despite starting out with unfavourable regional asset bases. This raises the question as to whether the strong emphasis on endogenous capabilities in EEG also provides a sound theoretical framework for explaining these tremendous diversification dynamics. This paper therefore aims to re‐evaluate the wider validity of the path‐dependent conceptualization of regional diversification in the context of a lower‐middle income economy. To this end, we analyse the diversification of Vietnamese regions between 2006 and 2015. In order to take into account context‐specific conditions that characterize Vietnam's economy, we add the role of foreign‐owned firms and state‐owned enterprises to the conceptualization of regional diversification processes. While the role of relatedness holds true for Vietnam, the presence of foreign‐owned firms allowed Vietnamese regions to break away from path dependency and diversify to unrelated industries. The findings highlight that only by adapting the analysis to context‐specific conditions are we able to understand how regional diversification takes place across different settings.